A PERSPECTIVE REVIEW ON APPLICATIONS OF NANOPARTICLE MEDIATED DRUG DELIVERY TO THE CNS - KEERTHANA, V.; DHANALAKSHMI, S.; HARIKRISHNAN, N. (International Journal of Current Pharmaceutical Research, 2020)
Delivery of drugs into the brain is one of the most interesting and challenging areas of research. The blood-brain barrier (BBB) is a highly selective semipermeable membrane that separates blood from the brain in the central nervous system. It acts as a barrier to protect the brain from microbes, neurotoxins and other chemical substances and also blocks the entry of many drugs into the brain. An estimated 6.8 billion people die every year from CNS diseases like Parkinson’s disease, Alzheimer’s disease, sclerosis, brain stroke, dementia and others. According to WHO, one billion people are affected worldwide, about 50 million suffer from epilepsy and 24 million suffer from Alzheimer and other dementias. This indicates the importance of the delivery of drugs into the brain for treating various neurological diseases and psychological disorders. In drug targeting, a concept was introduced by Dr. Paul Ehrlich as a ‘magic bullet’ that gave tremendous hope for the researches to deliver drugs into the brain. This review discuses about various drug targeting strategies and applications of nanotechnology in designing drug delivery systems with the ability to cross through the BBB for treating neurological diseases.